The ‘Price’ of the Rule of Law - Gyeney Laura; Szabó Maja (HUNGARIAN YEARBOOK OF INTERNATIONAL LAW AND EUROPEAN LAW, 2025)
On 15 December 2022, the Council of the European Union adopted Implementing Decision 2022/2506, setting out measures to protect the EU budget against breaches of the rule of law in Hungary. Perhaps the most notable aspect of this Implementing Decision is the prohibition on the Commission entering into legal commitments with Hungarian public interest asset management foundations (known as “KEKVAs”) and legal entities maintained by them. As a direct consequence of this sanction, Hungarian higher education institutions that have changed their model and are maintained by KEKVAs have been excluded from EU mobility (Erasmus+) and research (Horizon Europe) programmes. Six Hungarian higher education institutions have filed annulment actions against the Implementing Decision with the General Court. This study examines the well-foundedness of the legal arguments presented in these actions and their likely chances of success, based on the case law of the CJEU.